2021
DOI: 10.3390/ijms222011254
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Aminobutyric Acid (GABA) Promotes Growth in Zebrafish Larvae by Inducing IGF-1 Expression via GABAA and GABAB Receptors

Abstract: Insulin-like growth factor-1 (IGF-1) primarily increases the release of gamma-aminobutyric acid (GABA) in neurons; moreover, it is responsible for the promotion of longitudinal growth in children and adolescents. Therefore, in this study, we investigated whether exogenous GABA supplementation activates IGF-mediated growth performance. Zebrafish larvae treated with GABA at three days post fertilization (dpf) showed a significant increase in the total body length from 6 to 12 dpf through upregulation of growth-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…They are rich in protein, minerals, and various essential amino acids [ 9 ]. GABA is a non-protein amino acid that functions as a primary inhibitory neurotransmitter for the central nervous system and contributes to motor control, GH secretion, and emotion regulation [ 7 , 20 ]. Oysters contain a small amount of GABA, but not enough to promote their use as a functional food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are rich in protein, minerals, and various essential amino acids [ 9 ]. GABA is a non-protein amino acid that functions as a primary inhibitory neurotransmitter for the central nervous system and contributes to motor control, GH secretion, and emotion regulation [ 7 , 20 ]. Oysters contain a small amount of GABA, but not enough to promote their use as a functional food.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 plays a key role and has been shown to stimulate muscle cell proliferation and act as a regulator for both muscle protein synthesis and degradation [ 5 ]. Studies have proven that γ-aminobutyric acid (GABA) can directly or indirectly stimulate GH release and IGF-1 expression [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ultra-performance liquid chromatography (UPLC) for amino acids of FO revealed that FO contained approximately 24.5% GABA from the total amino acid content [ 21 ]. Furthermore, in our recent studies, we found that GABA directly regulated growth performances in zebrafish larvae through GABA A and GABA B receptors, indicating the potent influence of GABA in FO-mediated growth performances [ 27 ]. Nevertheless, the therapeutic and preventive effects of FO have not been elucidated in glucocorticoid-induced secondary bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Gamma-aminobutyric acid (GABA) is widely distributed in the peripheral endocrine organs, such as the pituitary [ 34 ]. A study conducted by Athapaththu, A. et al found that GABA induced IGF-1 expression through GABA(A) and GABA(B) receptors and promotes the growth rate of zebrafish larvae through the IGF-1-IGF-1R axis [ 35 ]. Moreover, the malfunction of signaling molecules in the CCK/SRC/PI3K cascade reaction with leptin/JAK2/PI3K/STAT3 signaling pathway may lead to eating disorders [ 36 ].…”
Section: Discussionmentioning
confidence: 99%